SEASONAL VARIATION OF PHENOLS, NITROGEN, FIBER, AND IN VITRO DIGESTIBILITY IN SWEDISH MOOSE - Palo, Thomas R; Jordan, Peter A; Pehrson, Åke; Staaland, Hans (Lakehead University, 2012)
Understanding how different components of food are processed and digested within the compartments of the digestive tract of large herbivores has important implications in their foraging behaviour, nutritional ecology, and techniques for measuring diet composition and nutritional quality of forage. Analysis of contents from different compartments of the digestive tract of moose in central Sweden showed that neutral detergent fiber (NDF) and nitrogen (N) content varied throughout the digestive tract and among individual moose (Alces alces). Total phenols (TP) had an inconsistent pattern throughout the digestive tract, possibly reflecting variation in diet composition and phenol patterns. The study moose were divided into 2 groups; the winter group had low N in the digestive tract and high NDF and dry matter content, and the summer group had high levels of N and low NDF and dry matter content. The phenol platyphyllane, indicative of consumption of dormant silver birch (Betula pendula), was detected throughout the contents of the digestive tract in 2 animals in the winter group. The winter moose had higher NDF than summer moose, indicating the seasonal change in diet quality. In vitro organic matter digestibility (IVOMD) was not different between the summer and winter diets. The effect of birch phenols on IVOMD was concentration-dependent; differences between seasons were apparent at only the highest concentration. The 2 groups had marked differences in digestive content of major nutrients, NDF, and ability to digest forage which were consistent with typical variation in seasonal diet quality.